A displaceable electrocardiogram electrode and a method for preparing the same
By adopting an improved conductive adhesive layer and electrode core design in the electrocardiogram, the existing electrocardiogram electrode has solved the problems of poor conductivity and low reuse rate, and the displaceable and efficient reuse of the electrocardiogram electrode is realized, reducing the cost of use and resource waste.
Patent Information
- Application Number
- CN202311271541.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The existing disposable electrocardiogram electrodes are small in size, poor viscosity and inability to displace and use, resulting in poor conductivity, low reuse rate, waste of resources and high usage costs.
A displaceable electrocardiogram electrode is designed, using a conductive adhesive layer composed of polyvinylpyrrolidone, polyaniline, polyethylene wax, silver powder and sodium stearate, combined with the electrode core and anti-mucosal layer, so as to improve the die-cutting ability and adhesion of the conductive adhesive layer, the electrode can be reused.
It improves the reuse rate of the electrocardiogram electrode, enhances the adhesion to the skin, reduces the peeling strength after the first fit, reduces interference and pain, and is easy to operate.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocardiograph electrodes, in particular to a displaceable electrocardiograph electrode and a preparation method thereof. Background Art
[0002] ECG electrodes are the parts of an ECG machine or ECG monitor that are connected or in contact with the body. ECG electrodes can transmit the electrical activity generated by the heartbeat to the ECG device and then convert it into an ECG waveform, thereby diagnosing diseases and guiding treatment. ECG electrodes include disposable and reusable. Disposable electrodes are metal films that can be directly attached to different parts of the body and are mainly used for ECG monitoring. Reusable electrodes are mainly used during ECG examinations and are part of the ECG machine.
[0003] Conventional disposable heart electrode patches are generally composed of a connection buckle, a pressure-sensitive adhesive, an electrode core, a conductive adhesive, and a protective layer (anti-adhesive film layer). The connection buckle is made of metal, the electrode core is generally made of acrylonitrile-butadiene-styrene-silver chloride, the pressure-sensitive adhesive is a medical tape composed of foam and polyurethane adhesive, the conductive adhesive is a hydrogel composed of conductive material and polymer resin, and the protective layer is a polymer release material, which needs to be torn off when used. The electrode buckle is tightly connected to the non-adhesive side of the medical pressure-sensitive adhesive below, the electrode core is closed and connected to the upper electrode buckle through the medical pressure-sensitive adhesive, the conductive adhesive is attached to the bottom of the electrode core, and there is a protective layer under the conductive adhesive and the medical pressure-sensitive adhesive to protect the indwelling needle application and the conductive adhesive from being dirty and contaminated. In the production process of the heart electrode patch, the conductive adhesive is an aqueous liquid material, which is dripped onto the electrode core, and then cured and cross-linked by UV ultraviolet light to solidify it into a conductive and sticky hydrogel.
[0004] The quality of ECG electrodes directly affects whether an ECG machine can be used normally. Existing disposable ECG electrodes often have the following disadvantages: due to the small area of colloid, the area in contact with the skin is also relatively small, so the conductivity is poor; the adhesive will dry after a long time; the adhesive is not very sticky and cannot be moved for use, the reuse rate is low, resulting in a waste of resources, and the cost of use is high. Summary of the invention
[0005] In view of the above problems existing in the prior art, the object of the present invention is to provide a displaceable ECG electrode and a preparation method thereof, thereby improving the reuse rate of the ECG electrode.
[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0007] A displaceable ECG electrode, the electrode comprising at least the following parts: a connecting buckle, an electrode core, a conductive adhesive layer, and an anti-adhesive film layer;
[0008] The conductive adhesive layer comprises the following components in parts by weight: 20-30 parts of polyvinyl pyrrolidone, 20-30 parts of polyaniline, 0.1-1 parts of polyethylene wax, 10-20 parts of silver powder, and 5-8 parts of sodium stearate.
[0009] Furthermore, the conductive adhesive layer comprises the following components in parts by mass: 26 parts of polyvinyl pyrrolidone, 25 parts of polyaniline, 0.5 parts of polyethylene wax, 15 parts of silver powder, and 6 parts of sodium stearate.
[0010] Furthermore, the silver powder contains 1% ammonium polyacrylate dispersant.
[0011] Furthermore, the thickness of the conductive adhesive layer is 1.5-2.5 mm.
[0012] Furthermore, the preparation method of the conductive adhesive is: mixing the raw materials according to their mass fractions, stirring and heating to 80-100° C., stirring and ultrasonicating in a vacuum environment, and reacting for 1-2 hours to obtain the conductive adhesive.
[0013] Furthermore, the electrode core comprises the following components by weight: 25-30 parts of copolymerized polyethylene, 30-40 parts of kaolin, 12-18 parts of styrene-butadiene thermoplastic elastomer, and 1-3 parts of antioxidant.
[0014] Furthermore, the electrode core comprises the following components by weight: 28 parts of copolymerized polyethylene, 35 parts of kaolin, 16 parts of styrene-butadiene thermoplastic elastomer, and 2 parts of antioxidant.
[0015] Furthermore, the antioxidant is any one or more of diphenylamine, sulfate, bisphenol A, and thiobisphenol.
[0016] Furthermore, the preparation method of the electrode core is:
[0017] (1) Mixing and grinding copolymerized polyethylene, kaolin, styrene-butadiene thermoplastic elastomer, and antioxidant at a mixing temperature of 100-110° C. for a mixing time of 20-25 min, and screening through 120-150 mesh to obtain a mixture;
[0018] (2) The mixed material is granulated by a screw extruder at a granulation temperature of 220-240°C. The material is melted, stretched, cooled, and granulated by a granulator to obtain plastic particles with a diameter of 3-4 mm;
[0019] (3) The molten plastic particles are injected into the mold cavity and then cooled and formed. The cooling temperature is 20-25°C. The cooled semi-finished product enters the cutting machine and is cut into the required size as required to obtain the electrode core.
[0020] As described above, in the method for preparing the displaceable ECG electrode, when connecting the electrode core to the conductive adhesive layer, the electrode core needs to be heated to 70-80° C. before being bonded to the conductive adhesive.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The displaceable ECG electrode of the present invention improves the die-cutting ability of the conductive adhesive layer and reduces the peeling strength after the initial bonding through the combined effect of polyethylene wax and polyvinyl pyrrolidone. The ECG electrode can continue to be attached to another position after being torn off, and has a high reuse rate. It also has good adhesion to the skin, resulting in less interference with the electrode, less pain when peeling off the skin, and easy operation. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with specific embodiments.
[0024] In the following embodiments:
[0025] Polyvinyl pyrrolidone (CAS No. 9003-39-8) K-30 comes from Nanjing Chemical Reagent; polyethylene wax (brand name PEW-0320A) comes from Nanjing Tianshi New Materials; polyaniline (CAS No. 25233-30-1) comes from Aladdin Reagent; silver powder (product number S110972) comes from Aladdin Reagent; sodium stearate (CAS No. 822-16-2) comes from Nanjing Chemical Reagent; copolymer polyethylene (K38-20-123) comes from INEOS of the United States; kaolin (4000 mesh) comes from Qiangdong Mineral Products Processing Plant of Lingshou County; styrene-butadiene thermoplastic elastomer (brand name T171E) comes from Dushanzi Petrochemical Branch of PetroChina;
[0026] The rest are conventional commercially available chemicals.
[0027] Peel strength test method for initial bonding: Test the peel strength of the electrode in accordance with industry standard YY / T 0148-2006.
[0028] The peel strength test method for the second pasting is to peel off the ECG electrodes after the first pasting and then pasted again, and test the peel strength of the electrodes again in accordance with the industry standard YY / T 0148-2006.
[0029] The impedance of the electrodes was tested according to the industry standard YY / T 0196-94.
[0030] Example 1
[0031] A displaceable ECG electrode, the electrode is composed of: a connecting buckle, a pressure-sensitive adhesive, an electrode core, a conductive adhesive layer, and an anti-adhesive film layer, and its structure refers to Chinese patent ZL2020210149583.
[0032] The conductive adhesive layer comprises the following components in parts by weight: 20 parts of polyvinyl pyrrolidone, 30 parts of polyaniline, 0.1 parts of polyethylene wax, 10 parts of silver powder, and 8 parts of sodium stearate. The preparation method of the conductive adhesive is: mixing the raw materials according to the parts by weight, stirring and heating to 80° C., stirring and ultrasonicating under a vacuum environment, and reacting for 1 hour to obtain the conductive adhesive.
[0033] The electrode core comprises the following components in parts by weight: 25 parts of copolymerized polyethylene, 30 parts of kaolin, 12 parts of styrene-butadiene thermoplastic elastomer, and 1 part of antioxidant diphenylamine.
[0034] The preparation method of the electrode core is as follows:
[0035] (1) Mixing and grinding copolymerized polyethylene, kaolin, styrene-butadiene thermoplastic elastomer, and antioxidant at a mixing temperature of 100° C. for 20 min, and screening through 120 mesh to obtain a mixture;
[0036] (2) The mixed material is granulated by a screw extruder at a granulation temperature of 220°C. The material is melted, stretched, cooled, and granulated by a granulator to obtain electrode core particles with a diameter of 3 mm;
[0037] (3) The molten electrode core particles are injected into the mold cavity and then cooled to form. The cooling temperature is 20°C. The cooled semi-finished product is fed into a cutting machine and cut into the required size as required to obtain the electrode core.
[0038] The preparation method of the displaceable ECG electrode refers to the preparation method of the conventional disposable ECG electrode patch. Since the conventional conductive glue is an aqueous liquid material, it needs to be dripped onto the electrode core, while the conductive glue of the present invention is in a gel-like state and can be applied. It should be noted that the electrode core needs to be heated to 70~80℃ before being bonded with the conductive glue.
[0039] After testing, the peel strength during the first pasting was 3N, the peel strength during the second pasting was 2N, and the AC impedance of the electrode was 86Ω.
[0040] Example 2
[0041] A displaceable ECG electrode, whose structural composition is the same as that of embodiment 1.
[0042] The conductive adhesive layer comprises the following components in parts by weight: 30 parts of polyvinyl pyrrolidone, 20 parts of polyaniline, 0.3 parts of polyethylene wax, 12 parts of silver powder, and 5 parts of sodium stearate. The preparation method of the conductive adhesive is the same as that of Example 1.
[0043] The electrode core comprises the following components in parts by weight: 28 parts of copolymerized polyethylene, 35 parts of kaolin, 16 parts of styrene-butadiene thermoplastic elastomer, and 2 parts of antioxidant bisphenol A.
[0044] The preparation method of the electrode core is as follows:
[0045] (1) Mixing and grinding copolymerized polyethylene, kaolin, styrene-butadiene thermoplastic elastomer, and antioxidant at a mixing temperature of 110° C. for 25 min, and screening through 150 mesh to obtain a mixture;
[0046] (2) The mixed material is granulated by a screw extruder at a granulation temperature of 240°C. The material is melted, stretched, cooled, and granulated by a granulator to obtain electrode core particles with a diameter of 4 mm;
[0047] (3) The molten electrode core particles are injected into the mold cavity and then cooled to form. The cooling temperature is 25°C. The cooled semi-finished product is fed into a cutting machine and cut into the required size as required to obtain the electrode core.
[0048] The preparation method of the displaceable ECG electrode is the same as that in Example 1.
[0049] After testing, the peel strength during the first pasting was 2N, the peel strength during the second pasting was 1N, and the AC impedance of the electrode was 14Ω.
[0050] Example 3
[0051] A displaceable ECG electrode, whose structural composition is the same as that of embodiment 1.
[0052] The conductive adhesive layer comprises the following components in parts by weight: 26 parts of polyvinyl pyrrolidone, 25 parts of polyaniline, 0.5 parts of polyethylene wax, 15 parts of silver powder, and 6 parts of sodium stearate. The preparation method of the conductive adhesive is the same as that of Example 1.
[0053] The electrode core comprises the following components in parts by weight: 28 parts of copolymerized polyethylene, 35 parts of kaolin, 16 parts of styrene-butadiene thermoplastic elastomer, and 2 parts of antioxidant bisphenol A.
[0054] The preparation method of the electrode core is as follows:
[0055] (1) Mixing and grinding copolymerized polyethylene, kaolin, styrene-butadiene thermoplastic elastomer, and antioxidant at a mixing temperature of 105° C. for a mixing time of 22.5 min, and screening through a 135-mesh screen to obtain a mixture;
[0056] (2) The mixed material is granulated by a screw extruder at a granulation temperature of 230°C. The material is melted, stretched, cooled, and granulated by a granulator to obtain electrode core particles with a diameter of 3.5 mm;
[0057] (3) The molten electrode core particles are injected into the mold cavity and then cooled to form. The cooling temperature is 22.5°C. The cooled semi-finished product is fed into a cutting machine and cut into the required size as required to obtain the electrode core.
[0058] The preparation method of the displaceable ECG electrode is the same as that in Example 1.
[0059] After testing, the peel strength during the first pasting was 2N, the peel strength during the second pasting was 1N, and the AC impedance of the electrode was 26Ω.
[0060] Example 4
[0061] A displaceable ECG electrode, whose structural composition is the same as that of embodiment 1.
[0062] The conductive adhesive layer comprises the following components in parts by weight: 22 parts of polyvinyl pyrrolidone, 24 parts of polyaniline, 0.5 parts of polyethylene wax, 15 parts of silver powder, and 7 parts of sodium stearate. The preparation method of the conductive adhesive is the same as that of Example 1.
[0063] The electrode core comprises the following components in parts by weight: 30 parts of copolymerized polyethylene, 40 parts of kaolin, 18 parts of styrene-butadiene thermoplastic elastomer, and 3 parts of antioxidant bisphenol A.
[0064] The preparation method of the electrode core is as follows:
[0065] (1) Mixing and grinding copolymerized polyethylene, kaolin, styrene-butadiene thermoplastic elastomer, and antioxidant at a mixing temperature of 105° C. for a mixing time of 22.5 min, and screening through a 135-mesh screen to obtain a mixture;
[0066] (2) The mixed material is granulated by a screw extruder at a granulation temperature of 230°C. The material is melted, stretched, cooled, and granulated by a granulator to obtain electrode core particles with a diameter of 3.5 mm;
[0067] (3) The molten electrode core particles are injected into the mold cavity and then cooled to form. The cooling temperature is 22.5°C. The cooled semi-finished product is fed into a cutting machine and cut into the required size as required to obtain the electrode core.
[0068] The preparation method of the displaceable ECG electrode is the same as that in Example 1.
[0069] After testing, the peel strength during the first pasting was 2N, the peel strength during the second pasting was 1N, and the AC impedance of the electrode was 64Ω.
[0070] The industry standard YY / T 0148-2006 stipulates that the average force required for sticking the tape for every 1 cm width is not less than 1.0N. The initial peel strength of the ECG electrodes of the present invention is between 2 and 3N, and the peel strength during the secondary sticking is between 1 and 2N, both of which are within the prescribed range of the industry standard. In addition, the initial peel strength is not high, which makes it easier to shift and reduces the pain caused by the shift.
[0071] The industry standard YY / T 0196-94 stipulates that when a 10 Hz sinusoidal AC current is applied to an electrode pair, the AC impedance should not be greater than 3 kΩ. The present invention measures that the AC impedance of the electrode at 10 Hz is 10-100 Ω, which is much lower than the specified value of the industry standard.
[0072] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A displaceable ECG electrode, characterized in that: The electrode is composed of at least the following parts: a connecting buckle, an electrode core, a conductive adhesive layer, and an anti-adhesive film layer; The conductive adhesive layer comprises the following components in parts by weight: 20-30 parts of polyvinyl pyrrolidone, 20-30 parts of polyaniline, 0.1-1 parts of polyethylene wax, 10-20 parts of silver powder, and 5-8 parts of sodium stearate; The silver powder contains 1% ammonium polyacrylate dispersant; The thickness of the conductive adhesive layer is 1.5-2.5 mm; The preparation method of the conductive adhesive is as follows: mixing the raw materials according to their mass fractions, stirring and heating to 80-100° C., stirring and ultrasonicating under a vacuum environment, and reacting for 1-2 hours to obtain the conductive adhesive; The electrode core comprises the following components by weight: 25-30 parts of copolymerized polyethylene, 30-40 parts of kaolin, 12-18 parts of styrene-butadiene thermoplastic elastomer, and 1-3 parts of antioxidant; The electrode core comprises the following components by weight: 28 parts of copolymerized polyethylene, 35 parts of kaolin, 16 parts of styrene-butadiene thermoplastic elastomer, and 2 parts of antioxidant; The antioxidant is any one or more of diphenylamine, sulfate, bisphenol A, and thiobisphenol; The preparation method of the electrode core is as follows: (1) Mixing and grinding copolymerized polyethylene, kaolin, styrene-butadiene thermoplastic elastomer, and antioxidant at a mixing temperature of 100-110° C. for a mixing time of 20-25 min, and screening through 120-150 mesh to obtain a mixture; (2) The mixed material is granulated by a screw extruder at a granulation temperature of 220-240°C. The material is melted, stretched, cooled, and granulated by a granulator to obtain plastic particles with a diameter of 3-4 mm; (3) Inject the molten plastic particles into the mold cavity and then cool them to form. The cooling temperature is 20-25°C. The cooled semi-finished product enters the cutting machine and is cut into the required size as required to obtain the electrode core. When connecting the electrode core to the conductive adhesive layer, the electrode core needs to be heated to 70-80°C before bonding with the conductive adhesive.
2. The displaceable ECG electrode according to claim 1, characterized in that: The conductive adhesive layer comprises the following components in parts by weight: 26 parts of polyvinyl pyrrolidone, 25 parts of polyaniline, 0.5 parts of polyethylene wax, 15 parts of silver powder, and 6 parts of sodium stearate.
Citation Information
Patent Citations
Dense conductive rubber charging roller and production method thereof
CN101976023A
Medical bag
CN103841944A
Electrode core capable of preventing electrode buckle from being corroded and electrocardio electrode patch applying electrode core
CN214284937U
Water-based conductive adhesive and preparation method therefor
WO2022051961A1